ANALYSIS OF FACTORS THAT AFFECT CUSTOMER SATISFACTION IN CANDU SEDAYU COFFEE PRODUCTS - Cindy Afrita Sari; Wijianto Wijianto; Sri Hartono (Universitas Nusa Cendana, 2026)
This study is motivated by the increasing intensity of competition among manufacturers offering similar products, which has heightened the need to re-examine the determinants of customer satisfaction. In a highly competitive market environment, rising consumer demand requires firms to continuously enhance their value propositions. Accordingly, this research aims to assess the level of customer satisfaction with Sedayu Candu coffee products and to analyze the influence of product innovation, price, and customer experience on customer satisfaction. A quantitative research design was employed, with data analyzed using statistical techniques to test the proposed relationships. The findings indicate that product innovation, pricing, and customer experience have a significant positive effect on customer satisfaction. These results highlight the importance of strategic product development, competitive pricing, and the creation of positive customer experiences in sustaining customer satisfaction within the coffee industry. Keywords: Customer Satisfaction; Product Innovation; Price; Customer Experience; Customer Satisfaction